2021
DOI: 10.3390/en14051385
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for End-of-Life Coal Mine Sites: Black-to-Green Energy Approach

Abstract: This paper presents the possibilities of adapting active mines to generate green energy after their closure using their resources and/or infrastructure. For this purpose, firstly, the temporal horizon of selected mines in Poland was determined, its basic assumption being the analysis of the current state. In the research, 18 mining plants operating within 12 mines in the Upper Silesian Coal Basin (USCB) were analyzed. The analyzed mines belong to three of the five largest hard coal producers in Poland, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To ensure a smooth exit from coal, the European Commission established the Platform for Coal Regions in Transition [47]. Thus, the withdrawal from coal mining in most Western European countries is part of the EU climate and energy policy, which assumes achieving climate neutrality in the EU by 2050 [48][49][50]. Unfortunately, as the presented results of research conducted by the authors have shown, coal is often replaced with other fossil fuels, such as natural gas or crude oil.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure a smooth exit from coal, the European Commission established the Platform for Coal Regions in Transition [47]. Thus, the withdrawal from coal mining in most Western European countries is part of the EU climate and energy policy, which assumes achieving climate neutrality in the EU by 2050 [48][49][50]. Unfortunately, as the presented results of research conducted by the authors have shown, coal is often replaced with other fossil fuels, such as natural gas or crude oil.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Figure 1, in Europe, for example, the production of coal has been declining and has become residual. In fact, coal mining and extraction has been eliminated in countries such as the Netherlands (1970), Belgium (1990), France (2004) and Spain (2018) [1]. This is not limited to the European space; in fact, in recent years, the dominant position of coal in the energy consumption of China, the world's largest GHG emitter, has not changed, but the share of coal in its energy consumption has been decreasing year by year [2], so much so that the share of energy from natural gas and non-fossil fuels increased significantly from 17.9% in 2015 to 25.9% in 2022 [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is a complicated process connected not only with the transformation of the landscape but also closely related to spatial development, urban planning, housing, transport, social issues, the economy, and employment structure. Thus, the final phase of mining, that is closing mines down, is not the ultimate stage on the way to achieving the goals of the Green Deal, but just a step towards restoring full functionality to a given region [5]. Before it produces an intended effect, the revitalisation process of former mine areas can last for years and encounter numerous problems [6].…”
Section: Introductionmentioning
confidence: 99%